Aggression or Regression: A Comparative Study of Heroines in The Mill on the Floss and Pride and Prejudice - Abbasi, Pyeaam (k@ta: A Biannual Publication on the Study of Language and Literature, 2014)
The basic formula in the English Victorian novel seems to be an individual standing against the world (of the Victorian society). George Eliot‟s The Mill on the Floss (1860) and Jane Austen‟s Pride and Prejudice (1833) are two excellent examples of intellectual heroines standing against social expectations. This paper, as a comparative study, shows that in the former written by a romantic and modern novelist, the heroine drowns which signifies her self-renunciation and submission to the expectations of the society as well as her revenge of a body being shaped by Victorian ideologies. In the latter written by a conservative and realist writer, the heroine begins a process of education and transformation just to resolve her conflict in marriage. The paper concludes that in such novels the intellectual woman has to either submit to survive, or is wiped out which implies both the heroine‟s self-destruction of a Victorian body (aggression) or her drowning in the waters of ideology (regression).